1990
DOI: 10.1128/iai.58.5.1273-1280.1990
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma fermentans-derived high-molecular-weight material induces interleukin-6 release in cultures of murine macrophages and human monocytes

Abstract: A Mycoplasma fermentans-derived high-molecular-weight material (MDHM) is described which causes differentiation of concanavalin A-stimulated CBA/J or C57BL/6 mouse thymocytes to cytolytic effector T cells (CTLs). The effect of MDHM was inhibited by addition of monoclonal anti-interleukin-6 (IL-6) antibody. It could also be abolished after removal of adherent cells. However, adherent cell-depleted thymocytes could still form CTLs after addition of IL-6. The action of MDHM could thus be explained by the capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 23 publications
5
33
0
Order By: Relevance
“…Our results are in line with several recent publications reporting the upregulation of TNF-␣, IL-1␤, and IL-6 expression after stimulation of monocytes with mycoplasma-derived membrane fractions (16,22,25). Gamma interferon pretreatment of murine peritoneal macrophages was reported to induce large amounts of nitric oxide when the cells were subsequently stimulated with a mycoplasma-derived high-molecular-weightmaterial (MDHM) (22).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with several recent publications reporting the upregulation of TNF-␣, IL-1␤, and IL-6 expression after stimulation of monocytes with mycoplasma-derived membrane fractions (16,22,25). Gamma interferon pretreatment of murine peritoneal macrophages was reported to induce large amounts of nitric oxide when the cells were subsequently stimulated with a mycoplasma-derived high-molecular-weightmaterial (MDHM) (22).…”
Section: Discussionsupporting
confidence: 92%
“…Human monocytes can be triggered by a soluble entity, isolated from Mycoplasma arthritidis culture supernatant (4), that has been shown to be a basic protein of 20 to 25 kDa (15). Mycoplasma fermentans-derived high-molecular-weight material with a molecular mass of over 1.5 x 106 Da induces IL-6 production by human monocytes; this activity requires previous culture of mycoplasma with eucaryotic cells or extracts (19). Partial biochemical characterization of the molecular moiety of TUH-14 responsible for cytokine induction showed that it consists of five membrane-bound aryl lipoproteins with molecular masses of between 60 kDa and 80 kDa (23).…”
mentioning
confidence: 99%
“…38,39 M. fermentans has also been reported to induce a number of cytokines, such as interleukin-1 (IL-1), IL-6, granulocyte colony-stimulating factor, prostaglandins and tumour necrosis factor (TNF). [40][41][42] Christensen et al 43 reported that lymphotoxin, prostaglandin E 2 (PGE 2 ) and (in some people only) TNF would increase the 5 0 N activity of lymphocytes. The most effective was PGE 2 , which gave a threefold increase at the highest concentrations used (3 lM), whereas IL-6 had no effect.…”
Section: Discussionmentioning
confidence: 99%